SOSIALISASI PELAYANAN DAN PRODUK DI BANK MUAMALAT KCP BANYUWANGI - Pratiwi, Ana; Wahyuningsih, Lilis; Auliya Az, Shofia (Universitas Muhammadiyah Gresik, 2023)
In the world of banking business, customer satisfaction is one of the priorities, because it determines the success or failure of a banking business. Customers who are dissatisfied will certainly not choose the same banking services again, let alone supported by the many choices of other banking services (competitors), thus making customers have many comparisons to choose which bank is more suitable to their tastes and desires. In Banyuwangi there are many Islamic banking which provides a wide range of products. All of this is done so that customers become interested and ultimately choose the services they offer. In this study, we used a qualitative approach method. Where qualitative research produces descriptive data in the form of written or spoken words from people and observed behavior. With the steps that we do, namely: observation, interviews and documentation. and has the main goal of explaining the research object clearly and accurately by conducting ontological, epistemological, and axiological studies. Ontological analysis is an effort to find out service and product superiority, while epistemological analysis is to find ways or strategies to try to improve ontological analysis, and axiological analysis is to find out the benefits if sharia principles are applied to sharia banking.